2020
DOI: 10.3390/rs12244067
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Land Surface Temperature Change with Landsat Images during Dry Seasons in Bac Binh, Vietnam

Abstract: Global warming-induced climate change evolved to be one of the most important research topics in Earth System Sciences, where remote sensing-based methods have shown great potential for detecting spatial temperature changes. This study utilized a time series of Landsat images to investigate the Land Surface Temperature (LST) of dry seasons between 1989 and 2019 in the Bac Binh district, Binh Thuan province, Vietnam. Our study aims to monitor LST change, and its relationship to land-cover change during the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…In the case of Mérida, the difference in LST between urban areas and the peripheral areas with vegetation (scattered or dense) is on average 3.5 °C at the beginning and end of the study season, and is maintained in both seasons, similar to that observed by Adeyeri et al [78], Ferreira and Duarte [71], and Dang et al [79], among other authors.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the case of Mérida, the difference in LST between urban areas and the peripheral areas with vegetation (scattered or dense) is on average 3.5 °C at the beginning and end of the study season, and is maintained in both seasons, similar to that observed by Adeyeri et al [78], Ferreira and Duarte [71], and Dang et al [79], among other authors.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, specific sites with extreme temperatures were identified, associated with the cement industry, the sanitary landfill, fires, and burned areas as part of agricultural activities, in the same way it was observed that, in recent years, the temperature between these hot spots and the rest of city is increasingly similar, which shows the occurrence of the UHI. In big cities where the UHI phenomenon has been recorded, the heat island is concentrated in the center of the cities [22,24,78,79,81]. However, for Mérida's urban zone, the heat island is not located in the center, but in the periphery, where the new developments are located, as pointed out by Pérez-Medina and López-Falfán [68].…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that LST changes could be abnormal in some areas [7], resulting into droughts, increased frequency of fires, but simultaneously more rainfall and severe storms. LST and other parameters such as the normalized difference vegetation index (NDVI) or bare soil index (BSI) have been mostly studied in relation to urbanization [8,9]. Several studies have been conducted to analyze how changes in LST affect the variability of the microclimate of an area, the phenological cycle of vegetation [5,6], the agricultural production [10], and the land cover changes [11] using time series analysis of data.…”
Section: Introductionmentioning
confidence: 99%
“…LST is a very useful variable, which found its application in many different fields of science, including hydrology, climatology, geophysics, and specifically, in the assessment of the surface urban heat island [16,17]. LST is also recognized as complementary to nearsurface air and spatial temperature data in nature, thus helping to achieve the sustainable development of climate action goals [18,19]. One of the characteristics of the LST is that it shows very high spatial and temporal variation, mostly because of the heterogeneity of factors influencing its value, such as characteristics of the vegetation cover, precipitation, soil moisture, area topography, and geology [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%